2019
DOI: 10.1177/1071100719893334
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Preoperative Patient-Reported Outcome Measures (PROMs) to Postoperative Success in End-Stage Ankle Arthritis

Abstract: Background: Ankle osteoarthritis is a significant cause of pain and disability. Despite the effectiveness of treatments, a subset of patients remains with persistent pain and functional limitations. The purpose of this study was to use preoperative patient-reported outcome measures to predict which ankle osteoarthritis patients would be most likely to experience postoperative improvements in functional outcomes. Methods: A retrospective analysis of prospectively collected data was used to evaluate 427 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 17 publications
2
21
0
Order By: Relevance
“…Previous studies have used PROs to determine specific preoperative thresholds for achieving the MCID in foot and ankle surgery. 1,11,16,21 Ho et al 11 included 61 patients who underwent a variety of foot and ankle orthopedic procedures, including Achilles debridement, ankle arthroscopy, flatfoot correction, lateral ligament reconstruction, and bunionectomy. At an average follow-up of 9.9 months (range, 7.3-12.8 months), they reported a mean postoperative improvement of 8.4 and 3.9 in PROMIS PF and PI, respectively, and found that patients were likely to meet the MCID after surgery if their preoperative PROMIS PF was less than 29.7 and were unlikely to improve if their preoperative PROMIS PF was greater than 42.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used PROs to determine specific preoperative thresholds for achieving the MCID in foot and ankle surgery. 1,11,16,21 Ho et al 11 included 61 patients who underwent a variety of foot and ankle orthopedic procedures, including Achilles debridement, ankle arthroscopy, flatfoot correction, lateral ligament reconstruction, and bunionectomy. At an average follow-up of 9.9 months (range, 7.3-12.8 months), they reported a mean postoperative improvement of 8.4 and 3.9 in PROMIS PF and PI, respectively, and found that patients were likely to meet the MCID after surgery if their preoperative PROMIS PF was less than 29.7 and were unlikely to improve if their preoperative PROMIS PF was greater than 42.…”
Section: Discussionmentioning
confidence: 99%
“…2,21,39 Patients who fail conservative treatment of their ESAA are most commonly treated with either ankle arthrodesis (AA) or total ankle replacement (TAR). 14,32,40,42 AA is often recommended for younger Foot & Ankle International 00(0) and more active, high-demand patients or patients with comorbidities compromising soft-tissue healing 32,44 and TAR is often recommended for patients aged 65 years or older with lower demands. 44 TAR has become increasingly popular 35 and has been found to be more cost-efficient than AA among both older and younger patients.…”
Section: Introductionmentioning
confidence: 99%
“…14,32,40,42 AA is often recommended for younger Foot & Ankle International 00(0) and more active, high-demand patients or patients with comorbidities compromising soft-tissue healing 32,44 and TAR is often recommended for patients aged 65 years or older with lower demands. 44 TAR has become increasingly popular 35 and has been found to be more cost-efficient than AA among both older and younger patients. 12,34 To measure health-related quality of life, symptoms, and functioning from the patient's perspective, patient-reported outcomes (PROs) are increasingly being used.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations